DETERMINAN PENGEMBANGAN KARIR DAN MEDIASI KOMITMEN ORGANISASI PEGAWAI DINAS PUPR KOTA LHOKSEUMAWE - Julyadi Julyadi; Faisal Matriadi; Ikramuddin Ikramuddin (Universitas Malikussaleh, 2022)
This study aims to examine the Effect of Digital Leadership, Organizational Culture on Career Development through Organizational Commitment as a mediating variable at the Dinas PUPR Kota Lhokseumawe. The data used in this study were 121 employees using the Census method. The analytical tool used is Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) tools. The results show that digital leadership has no effect on organizational commitment, but has a significant effect on employee career development. Meanwhile, organizational culture has a significant effect on organizational commitment and employee career development. Furthermore, organizational commitment has a significant effect on the career development of Dinas PUPR Kota Lhokseumawe employees. Meanwhile, in indirect relationship testing, it was found that organizational commitment did not mediate the relationship between digital leadership and employee career development. But organizational commitment mediates the relationship between organizational culture and Career Development for Lhokseumawe City Public Works and Public Housing Service Employees.